Answer: (3x+2)(x+4)
Step-by-step explanation:Explanation:
3x2+10x−8
first multiply
3
with −8
and we get −24
then find two numbers that if we add or subtract we get
+10
and if we multiply we get
−24
and the numbers are
+12
and
−2
then we place those numbers as follow :-
3x2+12x−2x−8
then we group them
(3x2+12x)(−2x−8)
now take the common factor out.3x(x+4)−2(x+4)
then group the numbers outside of the brackets
(3x−2)(x+4)
Answer:
3 is greater than -4, but the line with slope -4 is steeper than the line with slope 3.
Step-by-step explanation:
3 is greater than -4, so strictly speaking, a slope of 3 is greater than a slope of -4.
On the other hand, the steepness of a line depends on the absolute value of the slope.
|3| = 3
|-4| = 4
Since 4 > 3, the line with slope -4 is steeper than the line with slope 3.
Answer: 3 is greater than -4, but the line with slope -4 is steeper than the line with slope 3.
2x + y = x - y - 3 = 6
Add 3 to everything
2x + y + 3 = x - y - 3 + 3 = 6 + 3
2x + y + 3 = x - y = 9
2x + y + 3 = 9
2x + y = 6 = x - y
Add y to everything
2x + 2y = 6 + y = x
Since x = 6 + y substitute every x with 6 + y
2(6 + y) + 2y = x
12 + 4y = x
This is as simplified as I can get and then just place 12 + 4y into every x in the original problem then solve
Answer: B
The series converges because it has a sum of 4.
Step-by-step explanation:
Answer:
c
Step-by-step explanatio answer c